The Vascular Access Related Infections: Have We Anticipated Them Adequately? - Erni Juwita Nelwan (Interna Publishing, 2022)
The number of patients in need of haemodialysis (HD) is increasing from time to time. In 2018, the Indonesian Renal Registry documented more than 130,000 active patients from 651 registered HD centres. Twenty percent are diabetic patients with end-stage renal disease (ESDR) equal to 8,633 patients. Diabetes Mellitus accounts for 2% of all diabetes cases in the age of 15 year-old and above. Hence, the increasing need for HD is inevitable and is parallel with the need for vascular access procedures. One of the major problems that occurs with vascular access is the risk of infection. Among HD patients, mortality and morbidity are predominantly associated with infection; about one-fifth as a cause of hospital admissions, one-fourth of the infection-related admissions are due to infection of vascular access. Susilo et.al, reported around 40% of patients with temporary vascular access had an infection. Data is limited and might be also underestimated. Unfortunately, the available studies examining risk factors for vascular access-associated infection are scarce and mostly collected with substandard methodology. It is to be highlighted that the study of Susilo et al. may represent the population of a  referral hospital for HD, yet as a reader it is worth noting that heterogeneity among centres and populations should be acknowledged. A comprehensive in-depth review and further research of these studies are crucial for a greater level of understanding for the cause of infection and therefore inform effective early detection and prevention strategies to reduce morbidity and mortality among haemodialysis patients, especially at-risk patients.